THE EFFECT OF WORK DISCIPLINE, TIME MANAGEMENT SKILLS, AND SELF EFFICACY ON EMPLOYEE PERFORMANCE MITRA SWALAYAN PURWODADI - Nanik Kumala Sari; Indah rahayu (LPPM Universitas An Nuur, 2025)
Background : The development of the retail industry is progressing very rapidly, this progress is supported by several factors, namely the development of science and technology, so that in order to maintain the progress of the retail industry so that it runs competitively, companies need to manage their human resources as well as possible. Purpose: Based on the background and problem formulation that has been explained, the purpose of this study is to describe and analyze the influence of work discipline, describe and analyze time management skills, describe and analyze self efficacy on employee performance at Mitra Swalayan Purwodadi. Method : This research uses quantitative methods. The sample used in this study was 65 respondents with probability sampling techniques which included saturated sampling. Data analysis using Partial Least Square (PLS) Statistical analysis technique version 4.0. Conclusion : It can be concluded that work discipline, time management skills, and self efficacy play a role in improving employee performance. Suggestion : In this study, there is a gap between the research results and the results in the field, this is indicated by the results of the hypothesis test or statistical test, especially on time management skills which state that it has a high test value, but in reality in the field, time management skills are still less stable so that for future research it is necessary to conduct further research using the same model and topic but with different objects.